South Asia Economic Focus, Fall 2014 : The Export Opportunity - World Bank (Washington, DC, 2014)
Global recovery remains below expectations and uneven across major advanced economies. Monetary tightening in a recovering US economy and potential deflation in a weak Eurozone constitute sources of risk for developing and emerging market economies. Nonetheless, developing country growth remains fairly robust. Notably, India continues its path towards sustained and faster growth as well as macroeconomic stability thereby paving the way for a solid regional performance in South Asia. While the region’s external position has been further solidified, key domestic challenges include reducing risks on the fiscal side as well as sustaining investment and export growth through structural reform and prudent macroeconomic policy. The overall short and medium term outlook for South Asia points towards continued acceleration with potential downside risks concentrated on the fiscal and structural reform side. Future growth dynamics will increasingly depend on strong investment and export performance. While a challenging task, it may afford South Asia to significantly catch up with the fastest growing region - East Asia and Pacific. This edition’s special focus section takes a macroeconomic look at exports and their potential for becoming a permanent growth pillar in South Asia.